The Role of Pancasila in Facing Radicalism and Exclusivism in Indonesia as Bhineka Tunggal Ika - Juliana Tirza; Wiputra Cendana (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The purpose of this paper is intend to describe the role of Pancasila in dealing with radicalism and social exclusivism in the era of globalization. This paper also tends to see the impact of globalization on the spread of deviant views such as radicalism and social exclusivism. Finally, how is Pancasila as an ideology to stem radicalism and social exclusivism in the era of globalization in everyday life in the context of nationality in Indonesia. With the literature review method, the writer tries to find answers to the focus of the writing. It was found that cultivation and appreciation of the values ​​of Pancasila need to be instilled in oneself from an early age. Tulisan ini bermaksud mendeskripsikan bagaimana peran Pancasila dalam menghadapi radikalisme dan eksklusi sosial di era globalisasi? Bagaimana pula dampak globalisasi terhadap merebaknya pandangan-pandangan menyimpang seperti radikalisme dan eksklusi sosial? Terakhir, bagaimana Pancasila sebagai ideologi untuk membendung radikalisme dan eksklusi sosial di era globalisasi dalam kehidupan sehari-hari dalam konteks kebangsaan di Indonesia. Dengan metode tinjauan pustaka, penulis mencoba mencari jawaban atas fokus penulisan. Ditemukan bahwa penanaman dan penghayatan nilai-nilai Pancasila perlu ditanamkan pada diri sendiri sejak dini.